Association information sources of reproductive health with sexual behavior of adolescents in Indonesia - Mur Octaviani; Dewi Rokhanawati (International Journal of Health Science and Technology, 2020)
30% of female adolescents reported their first sexual intercourse at under the age of 15 years old on the grounds of being forced by their partners and 49% of female adolescents could not reject their partner's invitation. The lack of reproductive health information sources is a continuity issue that affects the health status of adolescents. Those who get reproductive health information from the surrounding environment with the same age group and have similar dating experience may increase the risk of misinformation. This research aims to know correlation between the information sources of reproductive health and sexual behavior of adolescents in Indonesia. This quantitative study used cross sectional approach, using data analysis of Indonesian Adolescent Reproductive Health Survey Year 2012 (10,980 men and 8,902 women). The data analysis used Chi Square. It shown with the value of x2 (30,511) with the significance value (p = 0,000 0,05) and 95% CI. There is a correlation between the information sources of reproductive health and sexual behavior of adolescents in Indonesia. The assessment of Health Technology Assessment (HTA) on planning of WA Gateway based on Android application as Information Center and Adolescent Counseling can be the formulation of health policy with interactive learning media for adolescents.